2022
DOI: 10.3390/biology11010130
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of miRNAs in Embryonic, Larval, and Adult Lumpfish Provides a Reference miRNAome for Cyclopterus lumpus

Abstract: MicroRNAs (miRNAs) are endogenous small RNA molecules involved in the post-transcriptional regulation of protein expression by binding to the mRNA of target genes. They are key regulators in teleost development, maintenance of tissue-specific functions, and immune responses. Lumpfish (Cyclopterus lumpus) is becoming an emergent aquaculture species as it has been utilized as a cleaner fish to biocontrol sea lice (e.g., Lepeophtheirus salmonis) infestation in the Atlantic Salmon (Salmo salar) aquaculture. The lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 98 publications
(153 reference statements)
3
20
0
Order By: Relevance
“…Some mature miRNAs, like slu-mir-21-1-2-5p, slu-mir-22ab-3p, and slu-mir-26a-1-3-5p, were ubiquitously enriched throughout the stages. These mature miRNAs also had similar high abundances in all organs and developmental stages in other teleost fish [ 14 , 22 ]. Together, this indicates housekeeping functions that are conserved across species.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Some mature miRNAs, like slu-mir-21-1-2-5p, slu-mir-22ab-3p, and slu-mir-26a-1-3-5p, were ubiquitously enriched throughout the stages. These mature miRNAs also had similar high abundances in all organs and developmental stages in other teleost fish [ 14 , 22 ]. Together, this indicates housekeeping functions that are conserved across species.…”
Section: Resultsmentioning
confidence: 94%
“…In line with this is the finding that they regulate hox genes in Nile tilapia embryonic development [ 56 ] and also mediate cell proliferation and differentiation [ 57 ]. The mature members slu-mir-9-1-4-5p and slu-mir-7ab-5p have been reported as highly abundant in early developmental stages, as well as in the brain [ 14 , 22 , 58 , 59 , 60 , 61 ]. It is likely that their high relative abundance in early developmental groups in pikeperch reflect similar functions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But not only does the expression pattern of the protein-coding genes changes during development, the expression of ncRNAs, as regulators of the gene expression, is also fine-tuned during development. To obtain the complete miRNAome of lumpfish ( Cyclopterus lumpus ), Chakraborty et al [ 24 ] conducted miRNA analysis of different organs from adult individuals and entire embryos and larvae. They obtained 443 unique mature miRNAs from 391 conserved and eight novel miRNA genes, which represent an essential reference for future expression analyses.…”
mentioning
confidence: 99%
“…They obtained 443 unique mature miRNAs from 391 conserved and eight novel miRNA genes, which represent an essential reference for future expression analyses. Additionally, the expression patterns of specific conserved miRNAs in particular tissues and developmental stages indicated that they are involved in organ- and developmental stage-specific functions reported in other teleost [ 24 ]. To obtain as most complete as possible a first transcriptome of edible red sea urchin, Loxechinus albus was the objective of Antiqueo et al [ 25 ].…”
mentioning
confidence: 99%